2017
DOI: 10.1175/wcas-d-15-0070.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonmeteorological Influences on Severe Thunderstorm Warning Issuance: A Geographically Weighted Regression-Based Analysis of County Warning Area Boundaries, Land Cover, and Demographic Variables

Abstract: Studies have shown that the spatial distribution of severe thunderstorm warnings demonstrates variation beyond what can be attributed to weather and climate alone. Investigating spatial patterns of these variations can provide insight into nonmeteorological factors that might lead forecasters to issue warnings. Geographically weighted regression was performed on a set of demographic and land cover descriptors to ascertain their relationships with National Weather Service (NWS) severe thunderstorm warning polyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…While there have been a limited number of studies that have been conducted to quantitatively assess the potential impact of awareness of vulnerabilities on NWS product issuance (Davis & LaDue 2004;Dobur 2005;Barrett 2008;Barrett 2012;White & Stallins 2017;Naylor & Sexton 2018), this has generally remained an understudied topic. Most of these studies have confirmed what most operational meteorologists know -if there is a known concentration of people (i.e., a city or other municipality), it is more likely that that awareness of the assumed vulnerability of humans to severe weather will result in the higher likelihood of warning being issued on "marginal" events.…”
Section: Supportmentioning
confidence: 99%
“…While there have been a limited number of studies that have been conducted to quantitatively assess the potential impact of awareness of vulnerabilities on NWS product issuance (Davis & LaDue 2004;Dobur 2005;Barrett 2008;Barrett 2012;White & Stallins 2017;Naylor & Sexton 2018), this has generally remained an understudied topic. Most of these studies have confirmed what most operational meteorologists know -if there is a known concentration of people (i.e., a city or other municipality), it is more likely that that awareness of the assumed vulnerability of humans to severe weather will result in the higher likelihood of warning being issued on "marginal" events.…”
Section: Supportmentioning
confidence: 99%